2016
DOI: 10.1159/000443102
|View full text |Cite
|
Sign up to set email alerts
|

Gambogic Acid Inhibits Malignant Melanoma Cell Proliferation Through Mitochondrial p66shc/ROS-p53/Bax-Mediated Apoptosis

Abstract: Background/Aims: Malignant melanoma has high metastatic potential, is highly resistant to chemotherapy, and has a poor survival rate. Gambogic acid (GA), a polyprenylated xanthone extracted from a traditional Chinese medicinal herb, has been proven to exhibit antitumor activity. The present study aimed to investigate the signaling pathways that mediated GA-induced inhibition of human malignant skin melanoma proliferation. Methods: The study was conducted using A375 cells and the corresponding tumor transplante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…Multiple signalling pathways have been described for GA treatment of individual cancer cell lines . Our results and literature have shown inhibitory effect of GA in malignant melanoma . However, the mechanism of antitumour effect of GA in melanoma is not completely understood.…”
supporting
confidence: 48%
“…Multiple signalling pathways have been described for GA treatment of individual cancer cell lines . Our results and literature have shown inhibitory effect of GA in malignant melanoma . However, the mechanism of antitumour effect of GA in melanoma is not completely understood.…”
supporting
confidence: 48%
“…ARF can induce ROS generation, indicating that inhibitory role of p14 ARF in melanoma cell proliferation [29,30]. Xenografts in nude mice showed that the tumor volumes in the p16…”
mentioning
confidence: 99%
“…The tumor suppressor p53 plays a vital role in genome stability and p53 activation is a primary mechanism underlying pathological responses to DNA damaging agents such as chemotherapy and radiotherapy [12,13]. The proteins encoded by the TP53 gene bind to DNA, regulating gene expression and preventing genome mutation.…”
Section: Introductionmentioning
confidence: 99%